How Competence, Emotional Intelligence, and Affective Commitment Shape Employee Performance: Evidence from Central Java’s Fish, Animal, and Plant Quarantine Agency - Fransiska Desi Setyaningrum; Haryani Haryani; Lilik Setiawan; Albertus Martoyo (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the influence of competence, emotional intelligence, and affective commitment on employee performance at the Central Java Animal, Fish, and Plant Quarantine Agency. Employee performance is an important factor in supporting the effectiveness of public service organizations, particularly institutions responsible for quarantine supervision and biosecurity control. This research employed a quantitative approach using a survey method. The study population consisted of all employees at the Central Java Animal, Fish, and Plant Quarantine Agency, totaling 211 employees. A purposive sampling technique was applied, resulting in 129 respondents who met the criteria for analysis. Data were collected through questionnaires and analyzed using regression analysis with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method through the SmartPLS 3 application. The results of hypothesis testing show that competence has a positive and significant effect on employee performance. Emotional intelligence also has a positive and significant effect on employee performance. In addition, affective commitment positively and significantly influences employee performance. These findings indicate that employee performance can be improved by strengthening professional competence, emotional capacity, and organizational commitment.